PENGUJIAN KANDUNGAN ZAT PEWARNA RHODAMIN B PADA BEBERAPA JENIS MAKANAN DENGAN MINI SPEKTROFOTOMETER ABSORPSI PORTABEL - Nurul Halimah; Sri Suryaningsih; Jajat Y. Mindara; Sahrul Hidayat (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Rhodamine is kind of synthetic dyes that are widely used in textile and paper industries. The use of these hazardous substances rhodamine in foods and beverages is carried out by the manufacturers / community. Health impacts cause irritation of the respiratory tract, skin, eye, gastrointestinal, hepatic dysfunction and liver cancer. Thus, it is needed a study to detect rhodamine-B compounds in some foods and beverages by using a portable tool for practical and without having to do in the laboratory. This research was conducted with the stage of collection and sample preparation, validation of analytical methods, then analyzes the content of rhodamine in the test sample using a UV-Vis spectrophotometer and LCD mini tool. Based on the test results showed that the samples had a strong absorption of the green and blue LED RGB with highly sensitive to changes in the value of concentration. The test results s of mini absorption spectrophotometer concentrations of Rhodamine-B values ​​in samples of sauce at the peak wavelength of 532 nm is 2.39684 x ​​10-5 M, the value of the concentration of Rhodamine-B in the jelly in the peak wavelength of 532 nm is 2.78781 x 10 -5 M, and the value of the concentration of Rhodamine-B syrup at the peak wavelength of 486 nm is 1.75088 x 10-5 M.Keywords: Rhodamine-B, absorption, dyes, spectrophotometers.